x → 0 lim x 3 3 1 + tan x − 3 1 + sin x = k 1
Find the value of k satisfies the equation above.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Using Taylor expansions as x → 0 :
( 1 + x ) n = 1 + n x + O ( x )
tan x = x + 3 1 x 3 + O ( x 3 )
sin x = x − 6 1 x 3 + O ( x 3 )
The limit becomes
x → 0 lim x 3 1 + 3 1 tan x − ( 1 + 3 1 sin x )
= 3 1 x → 0 lim x 3 tan x − sin x
= 3 1 x → 0 lim x 3 x + 3 1 x 3 − ( x − 6 1 x 3 )
= 6 1
We can use binomial expansion to solve the question
lim x → 0 x 3 1 + 3 1 tan ( x ) − 1 − 3 1 sin ( x )
and apply L' Hospital's rule 3 times
Hello, I am very interested in your use of the binomial expansion. I tried to understand it online, but dont fully understand your way of doing it. Could you please develop your calculations? Thanks a lot!
Log in to reply
Hello, You can use binomial expression and omit the higher order terms the expression in
(
1
+
t
a
n
(
x
)
)
1
/
3
now you can apply binomial expansion to it. It will become
(
1
+
3
1
t
a
n
(
x
)
)
by approximation here follows the explanation what I have done .
https://math.stackexchange.com/questions/210110/whats-the-name-of-the-approximation-1xn-approx-1-xn
hope it helped
Thank you so much ! It is very clear now :)
Observe that from the algebraic identity: a 3 − b 3 a − b = ( a − b ) ( a 2 + a b + b 2 ) = a 2 + a b + b 2 a 3 − b 3 We could substitute a = 3 1 + tan x and b = 3 1 + sin x and by putting it into the limit, we get x → 0 lim x 3 3 1 + tan x − 3 1 + sin x = x → 0 lim x 3 ( 1 + tan x ) − ( 1 + sin x ) ⋅ 2 3 1 + tan x + 3 ( 1 + sin x ) ( 1 + tan x ) + 2 3 1 + sin x 1 = x → 0 lim x 3 tan x − sin x ⋅ 2 3 1 + tan x + 3 ( 1 + sin x ) ( 1 + tan x ) + 2 3 1 + sin x 1 The Maclaurin series for sin x and tan x is sin x tan x = x − 3 ! x 3 + 5 ! x 5 − 7 ! x 7 + … = x + 3 x 3 + 1 5 2 x 5 + 3 1 5 1 7 x 7 + … and using them to the left side fraction in the limit gives us = x → 0 lim x 3 ( x + 3 x 3 + 1 5 2 x 5 + 3 1 5 1 7 x 7 + … ) − ( x − 3 ! x 3 + 5 ! x 5 − 7 ! x 7 + … ) ⋅ 2 3 1 + tan x + 3 ( 1 + sin x ) ( 1 + tan x ) + 2 3 1 + sin x 1 = x → 0 lim x 3 2 1 x 3 + ( 1 5 2 − 5 ! 1 ) x 5 + … ⋅ 2 3 1 + tan x + 3 ( 1 + sin x ) ( 1 + tan x ) + 2 3 1 + sin x 1 = x → 0 lim ( 2 1 + ( 1 5 2 − 5 ! 1 ) x 2 + … ) ⋅ 2 3 1 + tan x + 3 ( 1 + sin x ) ( 1 + tan x ) + 2 3 1 + sin x 1 We could substitute x = 0 to the expression of the limit, it evaluates to 6 1 and hence k = 6 .
tan x = 1 + 3 x 3 + 1 5 2 x 5 + ...
sin x = x - 6 x 3 + 1 2 0 x 5 - ...
(1 + tan x)^(1/3) - (1 + sin x)^(1/3) = 6 x 3 + higher powers of x (using binomial expansion as |tan x| < 1 and |sin x| < 1 as x tends to 0)
Hence, the required limit is 1/6
Problem Loading...
Note Loading...
Set Loading...
Let 3 1 + tan x = A and 3 1 + sin x = B . L = x → 0 lim x 3 3 1 + tan x − 3 1 + sin x = x → 0 lim x 3 A − B Now, since A 3 − B 3 = ( A − B ) ( A 2 + A B + B 2 ) : L = x → 0 lim x 3 A − B × A 2 + A B + B 2 A 2 + A B + B 2 = x → 0 lim x 3 A 3 − B 3 × A 2 + A B + B 2 1 = x → 0 lim x 3 ( 1 + tan x ) − ( 1 + sin x ) × A 2 + A B + B 2 1 When x = 0 , A = 1 and B = 1 . This means the right side is defined for x = 0 , and we can remove it from the limit: L L = ( x → 0 lim x 3 1 + tan x − 1 − sin x ) × 1 2 + 1 × 1 + 1 2 1 = 3 1 x → 0 lim x 3 tan x − sin x Now we simply use L'Hospital's rule 3 times: L = 3 1 x → 0 lim 3 x 2 sec 2 x − cos x = 3 1 x → 0 lim 6 x 2 sec 2 x tan x + sin x = 3 1 x → 0 lim 6 2 sec 4 x + 4 sec 2 x tan 2 x + cos x = 3 1 × 6 2 + 0 + 1 = 3 1 × 6 3 = 6 1 Therefore k = 6